Cloud Security - A Semantic Approach in End to End Security Compliance - Chimakurthi, Venkata Naga Satya Surendra (Engineering International, 2017)
Many firms are seeing the benefits of moving to the cloud. For the sake of their customers’ data, cloud service providers are required by law to maintain the highest levels of data security and privacy. Most cloud service providers employ a patchwork of security and privacy safeguards while industry standards are being created. The upshot is that customers of cloud services are unsure whether or not the security protections supplied by these services are enough to meet their specific security and compliance requirements. In this article, we have discussed the many threats cloud users face and emphasized the compliance frameworks and security processes that should be in place to minimize the risk. To categorize cloud security measures, risks, and compliance requirements, we developed an ontology. We needed to design software to identify the high-level policy rules that must be applied in response to each danger as part of this initiative. Additionally, the program provides a list of cloud service providers that now satisfy specific security requirements. Even if they aren’t familiar with the underlying technology, cloud users may utilize our system to build up their security policy and identify compatible providers.